Granular particle-shape heterogeneous mixtures discharging through a silo. (11th February 2021) - Vamsi Krishna Reddy, A.; Kumar, Sonu; Anki Reddy, K.
Abstract: Abstract : Process industries often involve handling non-cohesive solid materials which vary in size and shape. A comprehensive understanding of such systems helps in effective handling of industrial operations. Here, we studied heterogeneous mixtures of dumbbells and discs flowing out of a two-dimensional silo using discrete element method simulations. We analysed discharge dynamics of the mixtures in two regimes, namely the free-flow regime ( W/d>=15 ) and the interrupted flow regime ( W/d<=10 ), where W and d are the orifice width and diameter of each of the circles of a dumbbell. One of the intriguing results is a decrease in the flow rate Q of mixtures with an increase in the fraction of dumbbells X_db in both of the regimes analysed. This can be attributed to the geometrical interlocking among the particles and a hindrance to the rotation of dumbbells. The time-averaged (coarse-grained) flow fields reveal an increase in the size of the stagnant zone beside the orifice with an increase in X_db . The stagnant zone hinders the particles flowing next to it, which is another reason for a decrease in Q with an increase in X_db . In the interrupted flow regime, we investigated clogged states of the mixtures using arch morphology, the fraction of dumbbells and number of particles in an arch, and avalanche sizes.